2023
DOI: 10.1155/2023/3166524
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pitaya Peel Supplementation on Nutritional Quality, Overall Sensory Acceptance, In Vitro Glycemic Index, and Antioxidant Release from Fiber-Enriched Cookies

Abstract: Pitaya peel is a by-product of fruit processing. In this study, the effects of pitaya peel supplementation in the cookie recipe on the nutritional quality, in vitro glycemic index, and antioxidant release from the enriched fiber cookies were investigated. The higher the ratio of pitaya peel powder (PPP) in the recipe, the greater the dietary fiber, betacyanin and phenolic contents, and antioxidant activities of the product. Cookies supplemented with 10–25% PPP were classified as having a low glycemic index, ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…The antioxidant activities of cookies with 40 % JFR powder were 12 times and 15 times higher than those of the control cookies, as quantified by DPPH and FRAP assays using Trolox as the standard, respectively. Similar improvement in dietary fiber and antioxidant contents of the fortified cookies is recently reported when food processing by-products such as pitaya peel [ 40 ] or spent green tea leaves [ 41 ] are added into cookie recipes.…”
Section: Resultssupporting
confidence: 70%
“…The antioxidant activities of cookies with 40 % JFR powder were 12 times and 15 times higher than those of the control cookies, as quantified by DPPH and FRAP assays using Trolox as the standard, respectively. Similar improvement in dietary fiber and antioxidant contents of the fortified cookies is recently reported when food processing by-products such as pitaya peel [ 40 ] or spent green tea leaves [ 41 ] are added into cookie recipes.…”
Section: Resultssupporting
confidence: 70%
“…According to the Codex Alimentarius (2013) Guidelines for Use of Nutrition and Health Claims ( 44 ), all pasta samples containing watermelon rind in this study were classified as high-fibre foods since their TDF content on dry mass basis was above 6 g/100 g. In addition, the IDF/SDF ratio of the high-fibre pasta samples progressively decreased when the sieve aperture size for watermelon rind powder was reduced from 400 to 149 µm. It can be concluded that all pasta samples supplemented with watermelon rind powder had an IDF/SDF ratio suitable for human consumption, since the ratio was almost within the range of [1-3] recommended by the American Dietetic Association ( 3 , 29 ). A high IDF/SDF ratio is usually observed in pasta fortified with cereal bran such as wheat bran (7.0) ( 3 ) or rice bran (9.0) ( 31 ).…”
Section: Resultsmentioning
confidence: 91%
“…It can be noted that the larger the particle size of watermelon rind powder, the more the antioxidant contents and activities released from the fortified pasta in the oral, gastric and intestinal phases of the in vitro digestion. It has been reported that many phenolic compounds in watermelon rind bind to dietary fibre in the plant cell wall ( 49 ) and could be released during human digestion ( 29 ). The bioaccessibility of total phenols and predicted glycaemic index of all pasta samples are shown in Fig 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations